Hierapolis, Athens and Rome: geographic rhetoric and The Second Sophistic - de Siqueira, Julio Cesar Piffero (Romanitas - Revista de Estudos Grecolatinos, 2019)
This work presents the geographic thought of Lucian of Samosta in the context of the second sophistic as a mean of a rhetorical construction of praise and blame related to centers of the Roman Empire. Lucian weighs and debates the discourse instigated by cities like Athens, Rome and the neighbor to his native city of Samosata, Hierapolis, or “Holy City”, according to the model of the epideictic discourse. Hence, we try to investigate how topics related to cities, travel and geography reflect in the formation of Lucian’s epideictic discourse as a means to confront and challenge the great issues that beset his generation. This paper, therefore, shall explore how Lucian constructs the map of the empire and situates himself within it, paying attention to its characterization of cities, and especially the epistemic hubris generated by the cultural intersections of the empire.